(untitled) (Research, Society and Development, 2022)
Milk is among the food more consumed by humanity. In this way, a study of its physical-chemical characteristics is justified to analyze if its components are by the legislation and if its hygiene conditions, more precisely the use of formaldehyde as a preservative, are established. The International Agency for Research on Cancer warns that formaldehyde has physicochemical properties that make it carcinogenic when consumed in food. In Brazil, the legislation does not establish minimum values for the presence of formaldehyde in foods of animal origin, and the technique suggested by the Ministry of Agriculture, Livestock, and Supply is a qualitative test. With the large consumption of milk by the Brazilian population and because it is a food subject to adulteration. The present work sought to analyze milk in terms of its physical-chemical characteristics (fat, density, freezing point, non-greasy solids, lactose, and proteins) and develop a methodology to analyze formaldehyde derivatized with 2,4-dinitrophenylhydrazine in milk samples using gas chromatography coupled to mass spectrometer.